Analisis Spasial Potensi dan Pengembangan Pariwisata Menggunakan Metode Analitycal Hierarchy Process (AHP) (Studi Kasus : Kecamatan Sungai Pagu Kabupaten Solok Selatan) - Na’imah Tulhasnah; Dwi Marsiska Driptufany; Ilham Armi (Jurnal Sains dan Ilmu Terapan, 2024)
Sungai Pagu District has rich natural and cultural tourism potential, but its management has not been optimal due to a lack of community involvement, limited budget, and insufficient human resources in the tourism sector. With the development of Geographic Information System (GIS) technology, it can be utilized in various survey, mapping, and spatial analysis projects. This study aims to analyze the tourism potential and determine the priority for developing tourist attractions in Sungai Pagu District using the Analytical Hierarchy Process (AHP) approach. The criteria used include Tourist Attractions, Facilities, Accessibility, Infrastructure, and Management, with alternatives being natural and cultural tourism. Data were collected through documentation, interviews, questionnaires, and observations, and then analyzed using Microsoft Excel software. The research findings show that there are 3 natural tourist attractions and 5 cultural tourist attractions. Based on the evaluation of 5 criteria, Management received the highest score (58.23%). Among natural tourism, Embung Batu Anyuik is the top priority (67.15%), while among cultural tourism, Menara Songket ranked the highest (40.67%).